Can Virtual Reality Ever Be Implemented in Routine Clinical Settings? A Systematic Narrative Review of Clinical Procedures Contained Within Case Reports for the Treatment of PTSD - Best, Paul; McKenna, Alison; Quinn, Paul; Duffy, Michael; Van Daele, Tom (Frontiers in Virtual Reality, 2020)
The evidence base for the use of immersive technologies, such as Virtual Reality (VR), for the treatment of Post-Traumatic Stress Disorder (PTSD) is compelling. Despite promising results wide spread use and adoption of this technology within routine clinical practice remains limited. A lack of detailed technical guidelines might be one of the reasons that hamper such uptake. To address this gap, the current review focuses on earlier design types, namely Clinical Case Reports in order to uncover additional detail in relation to clinical presentations and unique technical procedures. Systematic searches returned 419 results with 15 studies meeting inclusion criteria. This included 13 single subject case reports studies and 2 case series, totalling 27 participants. Results show the use of VR technology to treat PTSD is mainly exposure based. When using such interventions clinicians should conduct a thorough assessment of their clients’ background, trauma memory and triggers in order to tailor the VR experience. They should also plan some early orientation work to help clients acclimatise to the new virtual environment. Gathering self-reported data every five minutes throughout exposure will help with client monitoring, alongside physiological data. The use of olfactory or tactile stimuli may also be helpful during exposure, but is not a necessity. In conclusion, the costs of VR equipment have dropped significantly in the past years making this more accessible and affordable for healthcare providers. Nonetheless, a significant gap remains regarding the use of VR interventions for PTSD in clinical practice. The dearth of qualitative data available within the case report literature, might however help to bridge this gap.